The Effect of Discrete Emotions on Cognitive Control - Agarwal, Khushi (My University, 2023)
The Discrete emotion theory states that specific emotions are biologically determined and universal irrespective of ethnic and cultural differences. Each of these emotions should have a typical influence on our cognition. The current study is an attempt to study this theory by undertaking two discrete emotions, each from positive and negative valences and explore their variable influence (if any) on cognitive control using the emotional face–word Stroop task. Between the two tasks for each of the participants in the current study observed larger stroop effect among participants for face detection in comparison to word detection stroop task. However, the overall stroop effect was comparable across the four emotions within each task. The study was unable to find a variable effects of discrete emotional words on cognitive control in a face-word stroop task. The study implicates addition in terms of the use of discrete emotional face stimulus in combination with discrete emotional words to examine discrete emotion hypothesis.
Keywords: Discrete Emotions; Conflict monitoring; State and Trait Anxiety; Face-Word; Stroop Task